Analysis of environmental impact on emotional health of people visiting temples of Vrindavan, India: a qualitative survey - Shoor, Purva; Bhatt, Bhumika (International Journal Of Community Medicine And Public Health, 2019)
Background: In this century, blind faith in unhealthy environments is dwindling and more focus on environmental impact on a truly spiritual and emotionally uplifting experience is regarded as most important to contemporary visitors to sacred places. The main objective is to describe the emotional state of people visiting temples of Vrindavan and to describe the viewpoints on environmental factors affecting their emotional health. Methods: Type of study: a qualitative survey, study population: visitors to temples of Vrindavan. Method of sampling: purposive sampling, sample size: 67 people, study tool: pre-tested, semi-structured questionnaire for interview, data was analyzed using Microsoft Excel spreadsheet, and tabulated. Results: 82.09% of people interviewed were of the age 18-50 years. Among the visitors all were Indians, and one NRI. Majority interviewed were males. 6 people visiting temple 1 reported feeling annoyed, disturbed and insecure during visit. There were relatively positive responses regarding environmental factors due to religious constraints. Many people reported good conduct of pujaris (temple priests) in all the three temples with quite a few bad comments like professional seekers and greedy. Long queues and no comfort was disliked for all the three temples, however some people expressed no problem with it. Conclusions: Pilgrims do not critically analyze environmental aspects managed by authorities. They felt spiritual and emotionally aroused and preferred not to comment on not so comfortable experiences. We cannot neglect the rising exceptions to the usual herd of visitors who are on the rise.